Pengaruh Kepuasan Pelanggan Dan Citra Merek Terhadap Loyalitas Pelanggan Bengkel Mobil Di Kota Palembang - Teddy, Vincent Colin Jatmiko; Megawati, Megawati (MDP Student Conference, 2024)
this research aims to find out how customer satisfaction and brand image influence customer loyalty at car repair shops in Palembang City. The samples used in this research were people who had used car repair services in Palembang City, the number of samples taken was 257 respondents. The research method used in this research is a quantitative method. Determination of the sample using the purposive sampling method. The type of data used is primary data and the analysis method used is multiple linear regression with the SPSS application. The results of this research show that the variables of customer satisfaction and brand image have a positive and significant effect on customer loyalty at car repair shops in Palembang City